Protections, almukhalatat and naturalization, their impact on the historical reality of Muslim- Jewish relations in the nineteenth and early twentieth century in Morocco - ELQORCHI, Aicha (Journal of Humanities & Social Sciences, 2020)
In the nineteenth and early twentieth century, Morocco suffered as a result of the consular and diplomatic protection system which was a major cause of his fall under the yoke of colonialism, Thus system granted protection to Moroccan citizens, Muslims and Jews, they are exempted from paying taxes and even fail to fulfill their national duties claiming that they provide services for the benefit of those who protect them from consuls and European countries representatives.The danger of this system was manifested in the fact that it was mainly targeted at those who possess the country's greatest influence, Which contributed in damaging the prestige of the “Makhzen” at all levels. Where those who were under the protection outraged against those who weren’t protected, and they succeeded to the extent that the moroccan sultans could not grant rights to their owners due to the intervention of the protecting countries and the threatening to the “Makhzen” militarily if they don’t comply with the demands of those protected. A system that spread throughout the country and led it to move from the protection afforded to individuals to the protection imposed on the State in 1912.
Keywords: Muslim; Jew; protections; contacts; naturalization